A Case Study on Pompholyx (Dyshidrotic Eczema) w.s.r. to Vicharchika (AYUSHDHARA, 2022)
Besides the miraculous achievement of modern medical science, humanity is passing through a horror of disease and drug phobia, particularly in developing countries like India, where poverty and illiteracy account for the man’s ignorance towards the principles of health care. Skin is one of the five ‘Gyanindriyas’ as described in Ayurvedic texts. It is responsible for ‘Sparsha Gyan’ or touch sensation; therefore it plays a great role in physical and mental well-being of any individual. The skin is highly complex organ which plays a vital role in the body’s general working. The unbroken skin is the nature’s dressing over the body’s it acts as an effective barrier against the entry of diseases and its damage results in a whole host problems. Approximately 15% of all patients who visits the doctors to do for care of the skin as the wise saying ‘skin patients never cured and never die. When a skin disorder occurs it is rooted in tissues like fat, blood etc. Skin disorders occur due to aggravated Pitta Dosha. The built up toxins due to imbalanced Pitta cause Pompholyx. Pompholyx is a type of eczema, in which intensely itchy blisters that develop on the edges of the fingers, toes, palms and soles of feet appear. It may be acute or chronic and it affects teenagers and adults. In the present case 42yrs old female patient, who presented with complaints of rash over palm of left hand associated with intense itching, deep seated oozing wound and burning sensation has been presented here. She was treated with Ayurvedic treatment regimen for 40 days and she recovered fully with no symptoms left.